Diabase Temper as a Marker for Laguna Ceramics. (1st October 2015) - Pailes, M. C.; Killick, D. J.; Mills, Barbara J.; Ferguson, T. J.
Abstract : The Western Keresan area consists of the present-day Pueblos of Laguna and Acoma. In the 1950s, Florence Hawley Ellis proposed that a high proportion of Laguna ceramics could be distinguished from the ceramics produced by Acoma and other population centers by the frequent use of diabase temper. We conducted a petrographic analysis of 51 ceramic sherds designed to test the veracity of this association. Historic period sherds from culinary and decorated vessels collected at the Pueblo of Laguna do in fact contain a predominance of diabase temper. A consideration of local geology indicates these vessels were almost certainly produced in the Laguna area. This report thus firmly establishes the utility of diabase temper as a diagnostic indicator of ceramic provenance for this important period of Pueblo history.